A tradução interlingual de fábulas para o ensino de português escrito no fundamental maior - SILVA, Adrielly de Kássia Silva da (2022)
This work has as goal promote the inclusion of deaf students from public schools. Having as theoretical basis, the studies of Quadros and Karnopp (2004); Dizeu and Caporali (2005) who investigate the gestural-visual language in other words, sign language, its importance in the process of construction of deaf people and its definition as language of Brazilian deaf community. This research also exposes the need of translators and interpreters of Sign language in educational system. From Lacerda (2013, 2019); Fernandes and Rios (1998), it is emphasized that there is a shortage, not only in school environment but in many social environments. As pedagogical proposal, it was suggested a Commented Didactic Sequence (CDS) to work the teaching of textual genre Fable, which looks to contribute to the teaching of written Portuguese to deaf students of 6th grade in Elementary school at the school Benvinda de Araújo Pontes in Abaetetuba – Pa. This proposal involves interlingual translation Portuguese-Libras of a Children and Youth children fable highlighting the importance of work with deaf literature as pedagogical resource in favor of inclusion in schools, benefiting the rescue of deaf history and culture.